Biomechanics of Lower Limb Prosthetics - Pitkin, Mark R.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The most outstanding feature of "Biomechanics of Lower Limb Prosthetics" is the demonstration of the practicality of biomechanics, when applied to lower limb prosthetics. Several original concepts are described, one of which, "rolling technology," has been implemented in prosthetic devices, while the principle of "reciprocal anti-resonance in locomotion" addresses future studies. A concept of anthropomorphicity presented by the author is a key tool in planning the design of an artificial limb or its components. Measurement procedures and equipment used in biomechanical laboratories are presented. The book demonstrates how the analysis of biomechanical data is a tool in the decision-making process of a prosthetic designer and clinician. The author shares his experience in the development of a protocol for biomechanics subject trials used in NIH-supported studies.
LOWER LIMB PROSTHESIS -- Importance of Increasing the Functionality of Lower Limb Prostheses -- Normalization of the Gait Characteristics as a Means to Increase a Prosthesis$1 (Bs Functionality -- Lower Limb Prosthesis as Biotechnical System -- BIOMECHANICS OF NORMAL GAIT AND CRITERIA OF THE ANTHROPOMORPHICITY OF PROSTHESIS -- Methods of Gait Analysis -- Ballistic Gait in Norm -- BALLISTIC GAIN ON PROSTHESIS -- Active and Passive Moments In Joints -- Model of the Step Cycle -- Compensatory Synergy During Gait on Prosthesis -- Modeling of One-Leg Balancing -- THEORY OF DESIGNING THE ANTHROPOMORPHIC LOWER LIMB PROSTHESES -- Synthesis of a Mechanism of Artificial Prosthetic Joint -- Development and Testing of the Prosthetic Ankle -- Development and Testing of the Prosthetic Knee Joint -- TESTING OF THE EXPERIMENTAL PROSTHESES -- Program -- Results -- Biomechanical Testing of the Rolling Foot with Adjustable Stiffness -- Monitoring -- PRINCIPLE OF SPECTRAL RECIPROCITY IN BIOMECHANICS OF LOCOMOTION AND REHABILITATION.s
Keywords: Medicine; Orthopedics; Physical therapy; Rehabilitation; Medicine & Public Health; Orthopedics; Rehabilitation Medicine; Physiotherapy